Multi-genre and Transdiscursive Textuality of Semezdin Mehmedinović’s (Trans) Novel Me’med, Red Bandana and Snowflake - RALJEVIĆ, Selma (Anafora, 2023)
Semezdin Mehmedinović’s 2017 hybrid (trans)novel Me’med, Red Bandana and a Snowflake (Me’med, crvena bandana i pahuljica) employs a conceptual art medium to present its content. Among others, it deals with the themes of identity, memory and memory loss, trauma, war, migration, belonging, nostalgia, health, family, love, and art. Being himself a transnational Post-Yugoslav Bosnian and Herzegovinian/South Slavic/Eastern European-American writer with immigrant experience, Mehmedinović challenges the normative conception of identity by exploring identity construction in terms of personal and social identity as well as of the identity of narrative that disrupt the idea of “pure” identity. In its multi-genre, trans-discursive and trans-artistic storytelling, the novel shows the need of abandoning the idea of pure identity and embracing instead hybridity, which, among other things, envisions a coexistence of differences, deconstructs the construction of binaries (whether between nations, cultures, races, classes, or genders), and also reflects and (re)shapes many key features of contemporary human experience, configuring the realm of transgressed “imaginary” borders and articulating a voice of unassimilable identity of alterity.